RISK FACTORS OF ARTERIAL HYPERTENSION IN ORGANIZED COHORT OF MALE EMPLOYEES OF THE MACHINE BUILDING PLANT - A. N. Britov; S. A. Tjupaeva; N. A. Eliseeva; A. N. Meshkov; A. D. Deev (Рациональная фармакотерапия в кардиологии)
Aim. To study the incidence of arterial hypertension (HT) and prevalence of risk factors and occupational factors (OF) among people with HT on the base of engineering plant within "The program of formation of healthy lifestyle and prevention of chronic non-communicable diseases among the contingent, attached for the medical assistance for the period 2012-2016".Material and methods. The study included men (n=586), aged 20-65 years – the workers of the engineering plant directly involved in the works in conditions of industrial occupational exposures. These specified works occupied not less than 50% of the general time, and work experience at the enterprise in examined workers was at least 5 years.Results. All examined people were divided into 2 groups according to the office blood pressure (BP) levels: without HT – 380 people (64.8%) and with HT – 206 patients (35.2%). HT was observed more often among people without higher education (39.2 vs 28.3%; р<0.07). The prevalence of morphological changes on the fundus of eyes was significantly different in hypertensive patients and people without HT (30.6% vs 21.3%, respectively; p<0.04), that appears to be evidence of early organ disorders. OF were found more often in the group of workers with elevated office BP (31.9% vs 23.2%; p<0.04). Metabolic syndrome were detected in 44.8% of hypertensive patients vs 22.4% in people without HT (p<0.001). The people with HT but without other components of metabolic syndrome were taken for particular analysis. In this group the higher education was also much less often (24.0% vs 57.6%; p<0.001), and OF (excluding work at the computer) were revealed more often (87.3% vs 80.2%; p <0.06).Conclusion. The development of HT in workers of engineering plant is influenced, firstly, by "traditional" risk factors – age and components of metabolic syndrome, and higher education is a kind of HT "anti-risk factor". OF were significantly more common in the group of workers with elevated office BP. Periodic checkups should be the routine method to identify chronic non-communicable diseases among people of working age.